Quantitative ethnobotanical documentation of medicinal plants used by the indigenous ati tribes in Panay Island, Philippines / Cecilia Salugta Cordero, Ulrich Meve and Grecebio Jonathan Duran Alejandro - Salugta Cordero, Cecilia; Meve, Ulrich; Jonathan Duran Alejandro, Grecebio (Universiti Teknologi MARA, Perak, 2022)
The Ati (Negritos) are the aboriginal people of the Philippines comprising of more than 25 tribal groups that are scattered in the major islands of the country. In Panay Island of Western Visayas, they are recognized as gatherers, sellers, and traders of medicinal plants. This study aims to document the medicinal plants used by the two Ati tribes in Panay Island. Semi-structured interviews were conducted to determine the therapeutic use of medicinal plants in ethnomedicine. Use value (UV), relative frequency citation (RFC), relative importance index (RI), informant consensus factor (ICF), and fidelity level (FL) were used to evaluate the plant importance and Jaccard's Index (JI) was used to determine the similarity of the medicinal plants between the study sites. A total of 160 medicinal plant species in 55 families and 144 genera were used to treat 93 diseases in 17 different disease categories. The family Fabaceae was best represented with 17 species. The leaf was the most frequently used plant part and decoction was the most common method of preparation. Musa x paradisiaca had the highest UV (0.69) and Blumea balsamifera had the highest RFC (0.56) and RI (0.89) values. Diseases and symptoms, signs or clinical findings of the respiratory system recorded the highest ICF (0.75) with high use report. Spondias purpurea, Gynura procumbens, and Cyanthillium cinereum had the highest FL (100%). The JI (29%) showed a low similarity of medicinal plant compositions between the study sites. This study serves as an ethnobotanical basis for further pharmacological research and investigations, and as an awareness for preserving cultural heritage, traditional knowledge, and biological diversity.